Mechanistic investigation of the surface blackening phenomenon in GH3625 nickel-based superalloy - Zhicheng Cheng; Yan Yang; Wenzhu Sun; Ao Jiang; Ying Han; Wei Yu (Journal of Materials Research and Technology)
Nickel-based superalloys are extensively used in applications requiring excellent mechanical properties at elevated temperatures. However, the occurrence of surface blackening has led to reduced production efficiency. To investigate the reasons for the surface blackening phenomenon, this study conducted a comprehensive analysis of the microstructure and composition of blackened samples using optical microscopy (OM), scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), electron probe microanalysis (EPMA), X-ray diffractometer (XRD), X-ray photoelectron spectroscopy (XPS), focused ion beam (FIB), and transmission electron microscopy (TEM). Additionally, the mechanisms of surface oxidation and carburization are explored through molecular dynamics simulations, examining the impact of different atmospheres on the thickness of the oxide layer and the formation mechanisms of both oxide and carbide layers. A comparative analysis is performed on the annealed surface morphology and microstructure of samples treated with and without oil treatment. The findings reveal that O2/CO2/H2O molecules form oxide and carbide layers through adsorption, bonding, and subsequent diffusion into the Ni matrix. The oxidation process begins with the adsorption and local dissociation of oxygen molecules on the alloy surface, followed by the segregation of Cr atoms and the inward diffusion of oxygen. Residual lubricants from the cold rolling process are identified as the primary sources of carbon and oxygen during subsequent annealing. The primary products of the reaction between the lubricants and the nickel-based alloy are Cr2O3 and NbTiC, which constitute the main phases of the blackened layer.